2020
DOI: 10.3390/plants9070909
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Trichome Distribution Pattern in Arabidopsis Reveals Gene Expression Variation Associated with Environmental Adaptation

Abstract: Gene expression varies stochastically even in both heterogenous and homogeneous cell populations. This variation is not simply useless noise; rather, it is important for many biological processes. Unicellular organisms or cultured cell lines are useful for analyzing the variation in gene expression between cells; however, owing to technical challenges, the biological relevance of this variation in multicellular organisms such as higher plants remain unclear. Here, we addressed the biological relevance of this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The point-pattern approximation that we refer uses the nearest neighbour distance (NND), where each individual trichome/stomate is considered as a point (Clark & Evans, 1954 ). Okamoto et al ( 2020 ) used the point–pattern approximation and a GL3pro:GL3-GFP reporter to monitor gene expression under control and heat treatments. They observed that the trichome patterning gene GL3 is expressed heterogeneously.…”
Section: Quantitative Methods To Study Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…The point-pattern approximation that we refer uses the nearest neighbour distance (NND), where each individual trichome/stomate is considered as a point (Clark & Evans, 1954 ). Okamoto et al ( 2020 ) used the point–pattern approximation and a GL3pro:GL3-GFP reporter to monitor gene expression under control and heat treatments. They observed that the trichome patterning gene GL3 is expressed heterogeneously.…”
Section: Quantitative Methods To Study Leavesmentioning
confidence: 99%
“…They observed that the trichome patterning gene GL3 is expressed heterogeneously. This finding suggested that the noise resulting from either the abundance of cellular components or environmental conditions may lead to variable patterns in a biological system (Okamoto et al, 2020 ). Therefore, to predict the regulatory pathways underlying the formation of a given pattern, this variability needs to be considered.…”
Section: Quantitative Methods To Study Leavesmentioning
confidence: 99%
“…The use of a dual reporter system in plants helped distinguish between extrinsic and intrinsic noise in Arabidopsis, and revealed that fluctuation in gene expression is coupled in neighboring cells in young leaves ( Araújo et al , 2017 ). The trichome distribution pattern also emerges stochastically, and the variability in the trichome distribution pattern correlated with stochastic cell to cell variation in GL3 expression ( Okamoto et al , 2020 ).…”
Section: Stochasticity In Cell Fate Determinationmentioning
confidence: 99%
“…Turing's article ' e chemical basis of morphogenesis' , inspired by the vision of D' Arcy ompson for a mathematical approach to biology ( ompson, 1917), has been highly influential in the field of biological pattern formation and the so-called Turing patterning is nowadays thought to explain phenomena ranging from asymmetric cell divisions, plant phyllotaxis, patterning of animal skin, bone, scale and feather patterns as well as ecosystem vegetation patterns (Turing, 1952). For plants, this range of processes has recently been further expanded to encompass plant vasculature cell wall patterning, pigment patterning of plant flowers and leaf trichome patterning (Nagashima et al, 2018;Jacobs et al, 2020, Ding et al, 2020, Okamoto et al, 2020).…”
Section: Figmentioning
confidence: 99%